2012
DOI: 10.1111/j.1748-5959.2011.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

G. Stanley Hall and an American Social Darwinist Pedagogy: His Progressive Educational Ideas on Gender and Race

Abstract: President G. Stanley Hall hung only a portrait of Ralph Waldo Emerson in his office at Clark University in Worcester, Massachusetts. The philosopher embodied Hall's most cherished mid-nineteenth century ideas that comprised part of his intellectual worldview. In the 1840s, Emerson reflected on his transcendental concepts of the common mind and instinct, which held all innate human knowledge and behavioral patterns, in his Essays:There is one mind common to all individual men. Every man is an inlet to the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…It must be acknowledged that the school deprives children of their basic right -the right to play; it strips them of their innate creativity and of their childhood itself; it "puts old people's heads on young shoulders." The goal of the educational process is to bring up a happy person who can fulfill himself in the world and find the joy in communicating with others (Goodchild, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It must be acknowledged that the school deprives children of their basic right -the right to play; it strips them of their innate creativity and of their childhood itself; it "puts old people's heads on young shoulders." The goal of the educational process is to bring up a happy person who can fulfill himself in the world and find the joy in communicating with others (Goodchild, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Dewey (1931) argues that disciplines should not be separate, but rather bring to life problems through real-world application in his book titled The Way Out of Educational Confusion which paved the way for integrating curriculum in classrooms through the 1950s. STEM education has also affected by Dewey's laboratory school reform and philosophies (Goodchild, 2012cited from. Sublette, 2013.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Öğretim programlarının bütünleştirilmesi fikri, eğitimcilerin gerçek hayat ile ilgili problemlerin ayrı ayrı disiplinlere bölünemeyeceğini fark etmeleriyle ortaya çıkmıştır (Wang ve diğ., 2011). Dewey (1931) disiplinlerin ayrık olmaması gerektiğini savunduğu The Way out of Educational Confusion adlı kitabı ile sınıflarda bütünleşik program uygulamalarının önünü açmış ve Dewey'in laboratuvar okulları ile başlattığı reform ve felsefesinden STEM eğitimi de etkilenmiştir (Goodchild, 2012'den akt. Sublette, 2013.…”
Section: Introductionunclassified
“…Studies that have identified recapitulation in early progressive education have either failed to explore fully its pervasiveness and ethnocentric/racist repercussions (Egan, 2002; Strickland, 1967), or they have been limited to studies of eugenics in education (Selden, 1999; Winfield, 2007), the education of African Americans (Anderson, 1988; Watkins, 2001), Native Americans (Adams, 1995; Jacobs, 2009), and foreign students under U.S. control (Coloma, 2009; Paulet, 2007) without tracing the impact of the theory on the broader curriculum for White students. Although some historians have addressed aspects of the impact of recapitulation theory on educational thinkers, this attention has largely been limited exclusively to so-called child study advocates such as G. Stanley Hall and the American followers of Johann Herbart (Cleverley & Phillips, 1986; Cremin, 1961; Curti, 1963; Garrison, 2008; Goodchild, 2012; Kliebard, 1995; Ross, 1972); Thomas Jesse Jones, architect of the social studies curriculum at the Hampton Institute (Kliebard, 2002; Watkins, 2001); and more recently—and controversially—the work of John Dewey (Fallace, 2010, 2011; Margonis, 2009; Sullivan, 2003). This study builds on this scholarship by demonstrating that the influence of the theory of recapitulation extended well beyond Dewey, Jones, Hall, and the Herbartians to key child-centered pedagogues such as Colonel Francis W. Parker, Lester Frank Ward, William Torrey Harris, Charles Judd, William Bagley, Charles Eliot, and many others.…”
Section: Literature Reviewmentioning
confidence: 99%